Rancang Bangun Sistem Deteksi Dini Status Gizi dan Risiko Stunting pada Balita berdasarkan Tinggi dan Berat Badan menggunakan Metode JST Backpropagation - Mukhamad Roni; Dahnial Syauqy; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Nutrition is a health status based on a balance between needs and nutrients. Toddlers can be said undernourished if the measurement of the W/A z-score <-2SD, and stunting if the measurement of the H/A z-score <-2SD. Currently, the determination of nutritional status and stunting is still using conventional measurements and matched with the standard book table of children's nutritional status from the Ministry of Health. Therefore, a system developed can detect weight and height as well as nutritional status and risk of stunting in toddlers. This system uses ultrasonic sensor HC-SR04 to measure height, load cell and HX711 module to measure weight and backpropagation NN to predict nutritional status in toddlers. The implementation of nutritional status with the backpropagation NN method is divided into 2, namely nutritional status with poor and good classes, and stunting risk with low and high classes. The system has a height of 125 cm and a square footing with a width of 30cm x 30cm. Using MLP Topology Workbench for data panning using 3 input layers, 12 hidden layers, and 1 output layer for each backpropagation NN implementation. The ultrasonic sensor test got an accuracy of 98.5%, the load cell sensor test got an accuracy of 94.7%, the test on the method got 100% accuracy, and the overall system test got an accuracy of 96.6%.